LRPPRC: A Multifunctional Protein Involved in Energy Metabolism and Human Disease - Cui, Jie; Wang, Li; Ren, Xiaoyue; Zhang, Yamin; Zhang, Hongyi (Frontiers in Physiology, 2019)
Pentatricopeptide repeat (PPR) family plays major role in RNA stability, regulation, processing, splicing, translation and editing. Leucine-rich PPR-motif-containing protein (LRPPRC), a member of PPR family, is a known gene mutation that causes Leigh syndrome French–Canadian. Recently, growing amount of evidence points out that LRPPRC dysregulation is related to various diseases ranging from tumours to virus infection. This review presents available published data on LRPPRC protein function and its role in tumours and other diseases. As a multi-functional protein, LRPPRC regulates a myriad of biological processes, including energy metabolism and maturation and export of nuclear mRNA. Overexpression of LRPPRC has been observed in various human tumours and is associated with poor prognosis. Downregulation of LRPPRC inhibits growth and invasion, induces apoptosis and overcomes drug resistance in tumour cells. In addition, LRPPRC plays a potential role in Parkinson’s disease, neurofibromatosis 1, virus infection and venous thromboembolism. Further investigating these new functions of LRPPRC should provide novel opportunities for better understanding of its pathological role in diseases from tumours to virus infection and as a potential biomarker and molecular target for disease treatment.